2019
DOI: 10.1021/acs.langmuir.9b00206
|View full text |Cite
|
Sign up to set email alerts
|

Smooth and Transparent Films Showing Paradoxical Surface Properties: The Lower the Static Contact Angle, the Better the Water Sliding Performance

Abstract: Smooth and transparent hydrophilic films showing excellent water sliding properties were prepared by using a sol–gel solution of 2-[methoxy (ethyleneoxy)10 propyl]­trimethoxysilane and tetraethoxysilane. The resulting hybrid films were statically hydrophilic (static water contact angles (CAs) were in the range of 30–45°), but water droplets (50 μL) could move smoothly on an inclined surface (minimum sliding angle was 6°) without pinning or tailing because of low CA hysteresis (5 ± 1°). Thanks to this hybrid fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Sliding and contact angles as well as wettability time [51] were measured by Dataphysics OCA-15EC (GmbH, Germany) using 10-μl droplets of double-distilled water. All measurements were measured under ambient conditions using an ASTM D-7334 standard procedure.…”
Section: Superhydrophobic Evaluationmentioning
confidence: 99%
“…Sliding and contact angles as well as wettability time [51] were measured by Dataphysics OCA-15EC (GmbH, Germany) using 10-μl droplets of double-distilled water. All measurements were measured under ambient conditions using an ASTM D-7334 standard procedure.…”
Section: Superhydrophobic Evaluationmentioning
confidence: 99%
“…To prepare liquid-like surfaces on a variety of substrates, in many cases, surfaces were precoated with a very smooth SiO2 thin layer before use [54][55][56]. In contrast to such approaches, the Hozumi group focused on a sol-gel method which can form homogeneous thin films with sufficient thicknesses on a variety of practical substrates without being affected by their surface roughness [29,31,[34][35][36][37][38][39]41,42]. Additional advantages of this sol-gel method include: 1) no special equipment or experimental conditions are required, 2) good reproducibility, 3) no pretreatment of the substrate is required/one-step deposition is possible, and 4) large area treatment is available.…”
Section: Sol-gel Hybrid Filmsmentioning
confidence: 99%
“…Although such liquid-like surfaces are promising, they have been generally prepared using very thin monolayers [19][20][21][22][23] or polymer films [24][25][26] (with thicknesses of 1−a few nm). Therefore, highly smooth and chemically reactive substrates like Si wafer and glass slides have been typically employed, while the use of common engineering materials, such as polymers, metals, and inorganic oxides, has been rarely seen [27][28][29][30][31]. Thus, the development of a simple, one-pot, and reproducible process to fabricate liquid-like surfaces showing excellent liquid sliding behaviors toward multiple liquids, independent of the substrate materials and their sizes, is still very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches focused on decreasing CA hysteresis through the preparation of extremely smooth liquid-infused (for example, slippery liquid-infused porous surfaces (SLIPS)) , or liquid-like surfaces have been reported. Various polar and nonpolar liquids can move smoothly and roll off these surfaces at low values without pinning and tailing in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…Various polar and nonpolar liquids can move smoothly and roll off these surfaces at low values without pinning and tailing in all cases. Several groups including the authors have previously reported that liquid-like surfaces resulting from high mobility of functional groups are superior to other low-hysteresis omniphobic surfaces because they do not rely on both complicated textures and perfluorinated compounds. , Various materials including specifically featured organosilane monolayers, poly­(dimethylsiloxane) (PDMS) thin films/brushes, PDMS-embed polyurethane (PU) or epoxy (EP)-based coatings, and sol–gel hybrid films have been widely used to prepare liquid-like surfaces. However, until now, most studies related to this research field have unsurprisingly focused on using silicon (Si) or glass substrates as model surfaces ,,,,,,,, because their surfaces are very smooth, show good affinity toward various silanizing reagents, and are thermally and chemically stable/durable during the reactions.…”
Section: Introductionmentioning
confidence: 99%